Pengaruh suhu rendaman dan media tumbuh terhadap daya kecambah benih dan pertumbuhan tanaman Indigofera zollingeriana - Firna Novita Yafur; Sientje D. Rumetor; Onesimus Yoku (Program Pascasarjana Universitas Papua, 2019)
Indigofera zollingeriana is one of legumes that contains high nutrient contents (crude protein: 29,16%±2,37%; fibres: 14,02±2,48%; Ca: 1,78-2,48%; P: 0,34-0,46% and protein digestibility: 82,3-86,3%). The purpose of the study was to identify and analyse the effect of initial water heat treatment and different media on seed viability and plant growth of Indigofera zollingeriana. This study will be an useful basic information on how to cultivate Indigofera zollingeriana as one of forage feed in Papua Barat (West Papua). The result of the study could be used by the farmers. The design of the study was using complete randomize design with two factors: water heat treatment and different media. Water heat treatments consist of two different temperatures: 70oC and 80oC, and growth media had three different media: 100%; 75% soil + 25% compos; 50% soil + 50% compos. Every treatment combination had three replicates so in total the study had 18 unit experiments. Time of germination (days), seed viability (%), plant height (cm/week), number of leaves (per week), leaf length and width (cm/week), stem and leaf ratio, root length (cm/week), number of root nodules. The results showed that time of germination and seed viability indicated the best result by using water heat treatment at 70oC. Combination of water heat treatment at 80oC and 100% of soil as growth media showed the highest plant growth, the most number and width of leaf of Indigofera zollingerian, while stem and leaf ratio and root length were high with combination of water heat treatment at 80oC and media with 50% soil and compos. The greatest number of nodules were found in the plants with water heat treatment at 80oC and media with 75% soil + 25% compos.